PWE-093 Screening with Holotranscobalamin is Superior to Serum B12 in Identifying Vitamin B12 Deficiency in Patients with Crohn'S Disease. (4th June 2013) - Ward, M G; Kariyawasam, V C; Blaker, P A; Patel, K V; Goel, R M; Sobczynska-Malefora, A; Ajaegbu, A; Harrington, D J; Anderson, S H; Sanderson, J D; Irving, P M
Abstract : Introduction: Risk factors for vitamin B12 deficiency in patients with Crohn's disease (CD) include ileal disease and previous ileal resections. Screening for B12 deficiency is traditionally through serum B12 which is relatively insensitive. Holotranscobalamin (holoTC) is a test that measures the metabolically active fraction of B12 available for cellular uptake and has been shown to perform better than traditional testing in identifying patients with functional B12 deficiency. We hypothesised that holoTC would identify B12 deficiency in patients with CD deemed to be B12 replete on traditional testing and sought to identify prevalence and risk factors within this population. Methods: Prospective study of consecutive patients with CD. Patients receiving B12 supplementation were excluded. Patients underwent paired serum B12 and HoloTC testing. Serum B12 < 107pmol/L or HoloTC < 25pmol/L was defined as B12 deficient. Intermediate HoloTC values between 25pmol/L and 50pmol/L underwent further assessment with methylmalonic acid (MMA), considered the gold standard in metabolic B12 deficiency. MMA > 280nmol/L in patients < 65 years of age and > 360nmol/L in patients > 65 years of age confirmed B12 deficiency. Risk factors for B12 deficiency were examined including Montreal classification, surgical history and the presence of ileal inflammation or stricture. Results: 70 patients who were not receiving B12 supplementation were included, (37 (53%) male, median age 37.5 years (IQR 28–47)). Disease location was ileal in 19 (27%), colonic in 19 (27%), ileocolonic in 32 (46%). 27 (39%) had undergone surgery, 22 (31%) an ileal resection. 18 (26%) were B12 deficient using HoloTC; 8 (11.5%) on HoloTC alone and 10 (14.5%) after MMA analysis on intermediate HoloTC results. Serum B12 testing identified 4 (5.7%) patients with B12 deficiency; 2 were functionally B12 deficient with HoloTC alone and 2 were replete when assessed by MMA. Ileal resection length > 30cm (OR 5.3, 95% CI 2.6–10.8, p < 0.0001), ileal inflammation (OR 11.3, 95% CI 3.48–36.9, p < 0.0001), ileal stricture (OR 6.1, 95% CI 2.8–13.7, p < 0.0001) and ileal resection (OR 5.0, 95% CI 2.3–10.7, p < 0.0001) were significant predictors of B12 deficiency on univariate analysis. Conclusion: HoloTC identifies vitamin B12 deficiency in a significant percentage of patients with CD otherwise considered replete on traditional testing. In addition serum B12 testing identifies patients who are not functionally deficient. Active ileal disease, ileal resection and ileal resection > 30cm were significant predictors of vitamin B12 deficiency. Disclosure of Interest: None Declared.